HIV treatment outcomes in Europe and North America: what can we learn from the differences?. Issue 5 (May 2014) - Ambrosioni, Juan; Nicolas, David; Agüero, Fernando; Manzardo, Christian; Miro, Jose M
<x xml:space="preserve">Abstract</x> The access to antiretroviral treatment has been largely enlarged in Europe and North America in recent years, due to treatment guidelines that recommend earlier initiation of therapy. However, there are differences and heterogeneities in the health systems and in access and retention to care between different countries and regions, and for different subpopulations among the same country that impact in the final goal, that patients remain undetectable and in good health.